2015
DOI: 10.1016/s1473-3099(15)00144-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation, biochemical, and haematological parameters and their association with outcome in patients with Ebola virus disease: an observational cohort study

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
198
4
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(223 citation statements)
references
References 18 publications
20
198
4
1
Order By: Relevance
“…From published articles and news reports, there were also likely 15 patients infected with EBOV in Europe during the epidemic (two imported cases, one infection identified in Spain and twelve medically evacuated patients), of whom three died (20%). By comparison, mortality for EBOV reported in treatment centres in West Africa was 37-74% 211,[219][220][221][222] . Advanced supportive care clearly improved patient survival.…”
Section: Discussionmentioning
confidence: 93%
“…From published articles and news reports, there were also likely 15 patients infected with EBOV in Europe during the epidemic (two imported cases, one infection identified in Spain and twelve medically evacuated patients), of whom three died (20%). By comparison, mortality for EBOV reported in treatment centres in West Africa was 37-74% 211,[219][220][221][222] . Advanced supportive care clearly improved patient survival.…”
Section: Discussionmentioning
confidence: 93%
“…Data for Sudan virus-infected (SUDV-infected) patients demonstrated liver and tissue injury, together with renal failure and possible acute pancreatitis (3). More recent reports of biological follow-up for isolated patients or cohorts have confirmed these results and suggested that rhabdomyolysis is a common features in EVD (4)(5)(6)(7)(8). We report here the clinical, virological, and biological parameters recorded for a cohort of EBOV-infected patients hospitalized in the Macenta and Nzerekore ETCs between December 2014 and January 2015 who did not receive any experimental EBOV-specific therapy.…”
Section: Introductionmentioning
confidence: 93%
“…E bola virus (EBOV) contains a single-stranded negative-sense RNA genome and constitutes, together with Marburg virus and Cueva virus, the family of Filoviridae, order Mononegavirales. Filoviruses cause a severe fever accompanied by gastrointestinal symptoms, vascular leakage, multiorgan failure, and shock (1,2). The reported case fatality rates can reach 90%.…”
Section: Importancementioning
confidence: 99%